Família e posiç\~ao de classe: A socializaç\~ao familiar pela privaç\~ao e a socializaç\~ao familiar protetiva - Vitor Matheus Oliveira de Menezes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This text is part of the project Radiografia do Brasil Contemporâneo, developed by the Ipea between 2015 and 2016. Particularly, by a qualitative approach, the research analyzes the trajectories of individuals living in the city of Salvador, capital of Bahia, noting the experiences of family socialization, the routes in educative institutions, and the occupational insertion, as well as the broader access to monetary resources. As a result, by focusing on the popular classes, the research elaborates two types of family socialization: family socialization by deprivation and protective family socialization.
Keywords: D10; J12; J13; M52; 330; family; class; work; education; socialization